AERONET Remotely Sensed Measurements and Retrievals of Biomass Burning Aerosol Optical Properties During the 2015 Indonesian Burning Season. Issue 8 (26th April 2019) - Eck, T. F.; Holben, B. N.; Giles, D. M.; Slutsker, I.; Sinyuk, A.; Schafer, J. S.; Smirnov, A.; Sorokin, M.; Reid, J. S.; Sayer, A. M.; Hsu, N. C.; Shi, Y. R.; et al.
Abstract: An extreme biomass burning event occurred in Indonesia from September through October 2015 due to severe drought conditions, partially caused by a major El Niño event, thereby allowing for significant burning of peatland that had been previously drained. This event had the highest sustained aerosol optical depths (AODs) ever monitored by the global Aerosol Robotic Network (AERONET). The newly developed AERONET Version 3 algorithms retain high AOD at the longer wavelengths when associated with high Ångström exponents (AEs), which thereby allowed for measurements of AOD at 675 nm as high as approximately 7, the upper limit of Sun photometry. Measured AEs at the highest monitored AOD levels were subsequently utilized to estimate instantaneous values of AOD at 550 nm in the range of 11 to 13, well beyond the upper measurement limit. Additionally, retrievals of complex refractive indices, size distributions, and single scattering albedos (SSAs) were obtained at much higher AOD levels than possible from almucantar scans due to the ability to perform retrievals at smaller solar zenith angles with new hybrid sky radiance scans. For retrievals made at the highest AOD levels the fine‐mode volume median radii were 0.25–0.30 micron, which are very large particles for biomass burning. Very high SSA values ( 0.975 from 440 to 1, 020 nm) are consistent with the domination by smoldering combustion of peat burning. Estimates of the percentage peat contribution to total biomass burning aerosol based on retrieved SSA and laboratory measured peat SSA were 80–85%, in excellent agreement with independent estimates. Key Points: AERONET Version 3 screening allows many more AOD especially at longer wavelengths than Version 2 for very high smoke AOD conditions Retrieved very high aerosol single scattering albedo and large fine‐mode particle size are consistent with aerosol dominated by peatland burning MODIS satellite retrieval algorithms of AOD (collection 6.1) screened out a significant number of high fine‐mode AOD days during the event